Teacher Education: pedagogue and art in higher education (Revista Educação, Artes e Inclusão, 2022)
The Pedagogy course is permeated by challenges that have consequences in professional practice. These are related to the education of the pedagogue and its relation to art. We address these challenges with reference to oficial and scholarly documents such as: Ferraz and Fusari (2010), Fontoura (2019), Gatti (2010), Pimenta and Lima (2012). We aim to address the educational importance of art, contextualize the education of the pedagogue for art teaching, report and analyze art experiences, presente and analyze the prior and current experience of students with art and their expectations. Fourteen students from the Pedagogy course of a higher education institution participated in the research. The results showed that participants were unaware of the contributions of art languages to the educational process. Contributions indicate the importance of: valuing art in Pedagogy courses; the development of institutional projects that include educational and cultural experiences and activities; participation in continuing education courses in art; the record of experiences with art teaching; promoting inclusive art experiences that go beyond the academic environment, involving both family and community by building outreach projects.
Keywords: Art; Pedagogy; teacher training